Pengaruh ROA, DER, Serta LDR Terhadap Harga Saham Perusahaan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2022-2025 - Vivin Shalsya Aulia; Rr. Eko Giyartiningrum (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
This study is underpinned by an attempt to examine the effects of ROA, DER, LDR on stock prices of banking sub-sector firms listed in Indonesia Stock Exchange during the 2022-2025. This study is justified by several contradictory prior research finding on the relationship of financial ratios to stock price, which it is hoped could be further investigated empirically. This study employs quantitative methodology with associative research design. The data employed in this study are secondary data consisting of annual financial statements and stock prices of banking firms. This study employs purposive sampling to select the research sample. The finding show ROA has a positive and statistically significant influence on stock prices. As for DER and LDR it does not exert any effect over stock prices. Simultaneously, ROA, DER and LDR also effect stock price. The findings indicate that financial performance information continues to be a key element to be considered by financier in making investment decisions and are in accordance with the Signalling Theory which states that corporate financial information as a signal to the market in seeing the prospects of the company in the future.